The cotyledon cell wall and intracellular matrix are factors that limit iron bioavailability of the common bean (Phaseolus vulgaris). Issue 7 (21st June 2016) - Glahn, Raymond P.; Tako, Elad; Cichy, Karen; Wiesinger, Jason
Abstract : Strategies that enhance the Fe bioavailability of the bean are of keen interest to nutritionists, bean breeders and growers. Abstract : Strategies that enhance the Fe bioavailability of the bean are of keen interest to nutritionists, bean breeders and growers. In beans, the cotyledons contain 75–80% of the total seed Fe, most of which appears to be located within the cotyledon cells. The cotyledon cell walls are known to be resistant to digestion in the stomach and the upper small intestine. Therefore, given the above and the general belief that the primary site for human Fe absorption is the upper small intestine, the present study was designed to determine if the cotyledon cell walls represent a barrier to Fe absorption from the bean. To do so, we utilized high pressure to rupture bean cotyledon cells. The iron bioavailability of cooked bean samples was assessed using an in vitro digestion/Caco-2 cell culture model. Microscopy analyses confirmed that the cotyledon cell walls are highly resistant to pepsin, the low pH of the stomach, and the pancreatic enzymes, indicating that the walls are a barrier to Fe absorption from the bean. Relatively high intracellular pressure (>4000 psi) was required to initiate cell wall rupture. Surprisingly, the lysis of cotyledon cells did not result in a consistent or strong enhancement of bioavailable Fe, suggesting that the liberated intracellular starch and protein influenced the Fe bioavailability by creating a matrix that inhibited the exchange of Fe with the cell transport mechanism. Such observations warrant further pursuit in vivo as the confirmation of these effects would reshape strategies to enhance Fe absorption from beans.